Dakwah Islam Melalui Bimbingan dan Konseling dalam Membangun Religiusitas Islami Anak Berkebutuhan Khusus - Mierrina, Mierrina (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Children with special needs are actually not different from children in general who are said to be normal, they are born by the will of God. Like children in general, children with special needs are born with both deficiencies and advantages. Children with special needs have difficulty levels due to physical, emotional, mental, social, and or have special intelligence and talents. Children with special needs require education and coaching as children in general or normal children. Children with special needs require assistance that involves educational activities, guidance and counseling in which contains the essence of religiosity, especially Islamic religiosity. In the mentoring process that leads to the establishment of Islamic religiosity for these special needs children, Islamic Da'wa land for certain community, that is children with special needs, involving the elements of parents, teachers, and society, in addition to children with special needs, Which will be done by a counselor. The counselor as a da'I will conduct guidance and counseling that focuses on the establishment of Islamic religiosity, which includes dimensions: (1) educational dimensions, (2) developmental dimensions, (3) preventive dimensions, (4) ecological dimensions (5) futuristic dimension. This is where the role of the counselor as well as the role of a da'i, becomes so important in conducting Islamic Da'wa activities, for the community especially for certain communities that is children with special needs with various elements involved in it.